Hubungan Keintiman Keluarga dengan Tingkat Kecemasan Pembalap Road Race di Surakarta - Mardiawan, Zulhilmi Bramantyo; Hadin, Yusviek; Yuliadi, Istar (Nexus Kedokteran Klinik, 2014)
Background:Racer is a dangerous profession or a high risk job that can cause a death. Family is a places for a child who wants some needs and get fulfillthe needs. Moral can influence on the quality of racing and anxiety level riders. This study aims to determine the relationship of family intimacy with the anxiety level rider road race in Surakarta. Methods:This study was an observational analytic cross-sectional approach. Subjects wereÂ  racer in Surakarta. Road race rider interviews were conducted with a questionnaire to determine the level of anxiety with T-MAS scale and intimacy of the family concerned with Instrument Family Intimacy. Data were analyzed with the Pearson product moment statistical test (Î± = 0.05). Results: Of the sample obtained 30 racers. The results of data analysis showed a correlation coefficient of 0, 740 and p-value = 0.000 <0.05, so there is a significant relationship between the level of intimacy with the family of the anxiety level rider road race in Surakarta. Conclusions:There is a statistically significant relationship between the level of intimacy with the family of the anxiety level racer in Surakarta. This suggests that the higher the level of family intimacy anxiety levels further down. Keywords:family intimacy, anxiety, racerÂ